2016
DOI: 10.1063/1.4941436
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure stability and ambient metastability of marcasite-type rhodium pernitride

Abstract: High-pressure stability, ambient metastability, and high-pressure crystal chemistry of chemical bonds of marcasite-type RhN2 have been investigated using a laser-heated diamond-anvil cell up to a pressure of 70.6 GPa. High-pressure in-situ X-ray diffraction and Raman scattering measurements revealed that the marcasite-type RhN2 structure is stable up to 70.6 GPa and exhibited an order of axial compressibility of βc > βb > βa. This indicates that single bonded nitrogen dimer (N-N) plays an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
4
13
0
Order By: Relevance
“…The deviation of this angle from the corresponding angle in the marcasite structure (90°) decreases with the pressure increase from 0.34(4)° at 39.3 GPa to 0.12(4)° at 51.7 GPa that is in agreement with the theoretical studies of Yu et al Arsenopyrite structure type is typical for dipnictides of group 9 metals MX 2 ( M = Co, Rh, Ir; X = P, As, Sb) . Our result disagree with works of Niwa et al,, who reported a marcasite‐type structure for RhN 2 on the basis of high‐pressure powder X‐ray diffraction. We should note, that it is rather challenging to recognize the peak splitting in a high‐pressure powder diffraction pattern (Figure j), as the high‐angle peaks are too weak to be clearly resolved.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The deviation of this angle from the corresponding angle in the marcasite structure (90°) decreases with the pressure increase from 0.34(4)° at 39.3 GPa to 0.12(4)° at 51.7 GPa that is in agreement with the theoretical studies of Yu et al Arsenopyrite structure type is typical for dipnictides of group 9 metals MX 2 ( M = Co, Rh, Ir; X = P, As, Sb) . Our result disagree with works of Niwa et al,, who reported a marcasite‐type structure for RhN 2 on the basis of high‐pressure powder X‐ray diffraction. We should note, that it is rather challenging to recognize the peak splitting in a high‐pressure powder diffraction pattern (Figure j), as the high‐angle peaks are too weak to be clearly resolved.…”
Section: Resultssupporting
confidence: 66%
“…The first indexing resulted in the orthorhombic lattice parameters ( a = 3.8540, b = 4.7106, c = 2.7068 Å) characteristic for marcasite type structure of rhodium pernitride RhN 2. , However, the detailed analysis of the diffraction pattern revealed several extra features that had to be explained. In particular, we observed that some of the reflections are split (Figure b–d).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the chemistry of nitrogen at high densities revealed the ubiquity of charged [N2] xdimers in binary nitrides. 12,13,[22][23][24][25][26][27][28][14][15][16][17][18][19][20][21] These were first discovered in the form of diazenides, [N2] 2-, in Sr8N4[N2]•(e -)2, Sr8N4[N2]2, SrN2, and BaN2, with N-N bond lengths of 1.22 Å, comparable to those in protonated diazene N2H2 (1.21-1.25 Å). [29][30][31] The family of compounds featuring charged dinitrogen species was later enlarged due to high-pressure synthesis of transition metals dinitrides (OsN2, IrN2, PtN2, TiN2) 20,23,24 displaying tetravalent [N2] 4anions with N-N bond distances of ~1.4 Å, similar to those in hydrazine N2H4 (1.47 Å).…”
Section: Introductionmentioning
confidence: 99%
“…At ambient conditions, the lattice constants of m-Zr02 and a-Bi2O3 are listed in table 1. The results are slightly larger than the experimental value [8,9], which are due to the systemic error in GGA. Electronic Structure.…”
Section: Resultsmentioning
confidence: 52%